Comparative pathogenesis of type 1 (European genotype) and type 2 (North American genotype) porcine reproductive and respiratory syndrome virus in infected boar - Han, Kiwon (BioMed Central, 2013)
BACKGROUND: Porcine reproductive and respiratory syndrome virus (PRRSV) now has two main genotypes, genotype 1 (European) and genotype 2 (North American). There is a lack of data on the comparison of pathogenicity of the two genotypes in boars. The objectives of the present study were to evaluate the amount of PRRSV present in semen over time and compare the viral distribution and microscopic lesions of type 1 and type 2 PRRSV-infected boars. METHODS: Twenty-four 8-month-old PRRSV-naïve Duroc boars were randomly allocated to 3 treatment groups. The boars in groups 1 (n = 9) and 2 (n = 9) were intranasally inoculated with type 1 or type 2 PRRSV, respectively. The boars in groups 1 (n = 6) served as negative controls. Semen and blood samples were collected up to 35 days post-inoculation (dpi), and necropsies were performed on 14, 21, and 35 dpi. RESULTS: There were no significant differences in the genomic copy number of PRRSV, microscopic testicular lesion score, number of PRRSV-positive germ cells, or number of apoptotic cells between the type 1 and type 2 PRRSV-infected boars throughout the experiment. Histopathological changes were manifested by the desquamation of spermatocytes and the presence of multinucleated giant cells in seminiferous tubules of both type 1 and type 2 PRRSV-infected boars. The distribution of PRRSV-positive cells was focal; the virus was found in single germ cells or small clusters of germ cells, localized to the spermatogonia, spermatocytes, spermatids, and non-sperm cells in type 1 and type 2 PRRSV-infected boars. CONCLUSIONS: The results of this study demonstrated that two genotypes of PRRSV do not have significantly different virulence toward the male reproductive system of pigs.